Combined size and shape optimization of structures with a new meta-heuristic algorithm - Dede, Tayfun; Ayvaz, Yusuf (ELSEVIER SCIENCE BV, 2015)
In this study, a new meta-heuristic algorithm called teaching-learning-based optimization (TLBO) is used for the size and shape optimization of structures. The TLBO algorithm is based on the effect of the influence of a teacher on the output of learners in a class. The cross-sectional areas of the bar element and the nodal coordinates of the structural system are the design variables for size and shape optimization, respectively. Displacement, allowable stress and the Euler buckling stress are taken as the constraint for the problem considered. Some truss structures are designed by using this new algorithm to show the efficiency of the TLBO algorithm. The results obtained from this study are compared with those reported in the literature. It is concluded that the TLBO algorithm presented in this study can be effectively used in combined size and shape optimization of the structures. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Teaching-learning-based optimization; Size optimization; Shape optimization; Truss structure; IMPROVED GENETIC ALGORITHM; TRUSS STRUCTURES; DESIGN OPTIMIZATION; TOPOLOGY OPTIMIZATION; LAYOUT OPTIMIZATION; DISCRETE; GEOMETRY; STRATEGY; Computer Science